The Influence of Transformational Leadership, School Culture and Work Motivation on School Effectiveness in Junior High School in Medan - Gunawan Gunawan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This research is a quantitative study that examines the participatory leadership model, school culture and motivation with school effectiveness with path analysis techniques. The respondents of this study were 343 teachers in Junior High Schools in Medan from 2,140 teachers in 44 State Junior High Schools. The findings of this study statistically show that simultaneously there is a positive and significant influence of transformational leadership and school culture on the work motivation of Junior High School in Medan teachers, where the effect is 5.9%. Likewise transformational leadership, school culture and work motivation have a significant and significant influence on the effectiveness of State Junior High Schools in Medan, which amounted to 13.7%.